Neuroprotective effect of Capsicum annuum var. abbreviatum against hydrogen peroxide-induced oxidative stress in HT22 hippocampus cells. Issue 12 (2nd December 2018) - Byun, Eui-Baek; Park, Woo-Young; Kim, Woo Sik; Song, Ha-Yeon; Sung, Nak-Yun; Byun, Eui-Hong
ABSTRACT: Phenolic compounds isolated from pepper ( Capsicum annum ) have been demonstrated to have neuroprotective effects, whereas the physiological properties of Capsicum annuum var. abbreviatum (CAA) have not been studied. Thus, we investigate the chemical composition and neuroprotective activity of CAA extract (CAAE) in HT22 hippocampus cells against H2 O2 -induced neurotoxicity. CAAE treatment resulted in a significant protection of H2 O2 -exposed HT22, this protection ultimately occurred through an inhibition of MDA and ROS levels and an induction of SOD activity. Furthermore, CAAE treatment reduced H2 02 -induced apoptosis though decreasing the expression of pro-apoptotic factors (Bax, cytochrome c, and cleaved caspases-3) while increasing the expression of the anti-apoptotic factors (Bcl-2), as well as the accumulation of nucleus-Nrf2-mediated HO-1 signaling. Interestingly, CAAE has a high concentration of unique phenolic compositions (chlrogenic acid, tangeretin, etc.) than other capsicum annum extracts. Altogether, these findings suggest that CAAE can be a useful natural resource for alleviating neurodegenerative diseases. Graphical abstract: : Neuroprotective effect of CAAE against H2 O2 -induced oxidative stress in HT22 hippocampus cells.